Commitments and flexibilities in the WTO agreement on subsidies and countervailing measures : an economically informed analysis / José Guilherme Moreno Caiado. - Caiado, José Guilherme Moreno (Cambridge international trade and economic law., 2019)
The ability of countries to promote and protect their domestic industries in the face of stiff global competition is an important consideration in any trading agreement. Member states of the World Trade Organization are expected to adhere to the WTO Agreement on Subsidies and Countervailing Measures, but to what extent do the WTO Members have policy space to subsidize their industries? Using an economically informed framework, Caiado examines the flexibilities countries may find at the WTO to grant subsidies and impose tariffs to protect designated industries. By testing the Treaty system of entitlements and enforcement mechanisms against the theory of incomplete contract, this work offers a comprehensive analysis of the capacity of the SCM Agreement to achieve its goal: the concomitant regulation of opportunistic behavior and assurance of ex post flexibility.